Automatic herding reduces labour and increases milking frequency in robotic milking. (March 2017) - Drach, Uri; Halachmi, Ilan; Pnini, Tal; Izhaki, Ido; Degani, Amir
Abstract : The motivation of cows to be milked is a key factor in the utilisation of milking robots. If a cow does not voluntarily attend a robot stall, fetching, that requires expensive labour, is required. This research suggests a new concept, herding all the cows to the milking robot using an automatic herding system (AHS). An AHS was built as a system of slow moving mobile fences controlled by an industrial controller. The AHS herds all the cows to the milking robot. The AHS was used in a commercial farm with two milking robots, and the experiment was conducted for three months. The dairy herd was divided into a reference group (43 cows) and an experimental group (38 cows). The AHS was used only with the experiment group. Milking frequency increased in the experimental group by 45.5% (1.89 milkings d −1 vs. 2.75 milkings d −1 ), while there was no major change in the milking frequency in the reference group 0.4% (2.38 milkings d −1 vs. 2.39 milkings d −1 ). Milk yield increased in the experiment group 15.7% (35.65 kg d −1 vs. 41.25 kg d −1 ). There was also no major change in the milk yield in reference group 4% (31 kg d −1 vs. 29.76 kg d −1 ). There was an 80% decrease in labour time for fetching the cows to the milking robot in the experimental group (5 h day −1 vs. 1 h day −1 ) while there was no change in labour for the reference group. The AHS was therefore associated with higher milking frequency, higher milk yield and labour reduction, hence economic benefits are expected for the system. Highlights: A development of a new concept of automatic herding of all cows to a milking robot. The research aim was solving the low milking frequency problem. A new automatic herding system was designed and applied in a commercial farm. The results show higher milking frequency, enhanced milk yield and labour reduction. Therefore, the economic benefits of the new system are apparent.